The molecular transition that confers voltage dependence to muscle contraction - Marina Angelini; Nicoletta Savalli; Federica Steccanella; Savana Maxfield; Serena Pozzi; Marino DiFranco; Stephen C. Cannon; Antonios Pantazis; Riccardo Olcese (Nature Communications)
Abstract What is the molecular origin of voltage dependence in skeletal muscle excitation-contraction? Cholinergic transmission to the muscle fiber triggers action potentials, which are sensed by voltage-gated L-type calcium channels (CaV1.1). In turn, the conformational changes in CaV1.1 propagate to and activate intracellular ryanodine receptors (RyR1), causing Ca2+ release and contraction. The CaV1.1 channel has four voltage-sensing domains (VSD-I to -IV) with diverse voltage-sensing properties, so the identity of VSD(s) responsible for conferring voltage dependence to RyR1 opening, is unknown. Using voltage-clamp fluorometry, we show that only VSD-III possesses kinetic, voltage-dependent and pharmacological properties consistent with skeletal-muscle excitability and Ca2+ release. We propose that the earliest voltage-dependent event in the excitation-contraction process is the structural rearrangement of VSD-III that propagates to RyR1 to initiate Ca2+ release and contraction.